Measuring the overeducation in Colombia - Salas - Sánchez, Ricardo Andrés; Hoyos - Delgado, William; Quiroga - Pérez, Brayan Stiven; Ramoni - Perazzi, Josefa (Universidad Francisco de Paula Santander, 2023)
Overeducation is a problem of inefficient allocation of human resources in productive activities. Different investigations highlight its consequences such as wage differences, unemployment especially among university graduates and, in the Colombian case, a low employability in the formal sector. In general, authors use different methods for its measurement, the most important being the subjective method, given by worker survey; the objective method, by database of information on individuals and the statistical method, in which deviations from the mean or median are used. Using information from the Great Integrated Household Survey 2022, this study seeks to quantify overeducation in Colombia from the statistical method and analyze its incidence according to interest groups. The results suggest a level of overeducation of 16.54%, a level of correct education of 61.15% and, finally, a level of undereducation of 22.31%.